Representation of Local Culture in Culinary Vocabulary: Analysis of Lexical and Cultural Meaning of Banyuwangi Using Language - Elita Ulfiana; Adista Nur Primantari; Ohod Faisal Ahmed Saleh (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2025)
This study aims to examine the cultural practices of the Using community in Banyuwangi through vocabulary that has been included in the KBBI entry, especially in the culinary vocabularies. The focus of this study is on literal and cultural meanings associated with ethnosemantic studies. This study uses a qualitative descriptive method. The data amounted to 20 vocabularies obtained through KBBI entries and interviews with informants from the indigenous Banyuwangi community. The analysis of this study shows that the culinary vocabulary of the Javanese Using dialect in the KBBI entry interprets culinary vocabulary not only as food. However, the vocabulary also has cultural values ​​and social beliefs that can provide deep meaning as a guideline for life in behaving, both in terms of how to be grateful and respect each other. Therefore, this study can increase understanding and appreciation of culture through language as an effort to preserve the cultural heritage of the Using community, Banyuwangi.   Penelitian ini bertujuan untuk mengkaji praktik budaya masyarakat Using Banyuwangi melalui kosakata yang sudah masuk pada entri KBBI khususnya ranah kuliner. Fokus penelitian ini adalah pada makna literal dan kultural. Penelitian ini menggunakan metode deskriptif kualitatif. Data berjumlah 20 kosakata yang didapatkan melalui entri KBBI dan wawancara informan dari masyarakat asli Banyuwangi. Analisis penelitian ini menunjukkan bahwa kosakata kuliner bahasa Jawa dialek Using di dalam entri KBBI, memaknai kosakata kuliner tidak hanya sebagai penganan saja. Namun, mempunyai nilai-nilai budaya dan keyakinan sosial yang dapat memberikan makna mendalam sebagai pedoman hidup dalam berperilaku baik dari segi cara bersyukur dan saling menghargai. Oleh karena itu, melalui penelitian ini dapat meningkatkan pemahaman dan penghargaan terhadap budaya melalui bahasa sebagai upaya pelestarian warisan budaya masyarakat Using, Banyuwangi.